The Urgency of Appointing a Notary as The Official for Creating Waqf Pledge Deeds (PPAIW) for Shares Based on Law Number 41 of 2004 on Waqf - Wahab, Abdul; Sambas, Nandang; Sumiyati, Yeti (Future Science, 2024)
The object of waqf known to the public up to this point is still synonymous with immovable property (fixed assets). In Indonesia, regulations related to waqf are governed by several laws, including Law No. 41 of 2004 on Waqf. However, there are no specific regulations regarding share waqf. Additionally, concerning the creation of share waqf pledge deeds by a notary as the PPAIW, the regulations on waqf pledges stipulated in Article 27 of the Minister of Religious Affairs Regulation No. 73 of 2013 on Procedures for the Waqf of Immovable and Movable Assets Other than Money state that a notary is appointed as PPAIW by a Ministerial Decree. To be appointed by the Minister as PPAIW, one must meet the requirements of being a Muslim, trustworthy, and certified in waqf competence by the Ministry of Religious Affairs. These requirements pose a barrier for notaries to become PPAIW because there has been no socialization and implementation of the competence certification requirement. Moreover, the requirement to be Muslim means that not all notaries can become PPAIW. The aim of this study is to understand the implementation of regulations regarding notaries as PPAIW in the creation of Waqf Pledge Deeds. This research is a type of normative juridical research, with a sociological juridical approach. The findings indicate that the regulation and implementation of notaries as PPAIW for shares are not yet clear and firm, necessitating a broader legal review in relation to the principle of the benefits of share waqf for the community.